INSTRUMENTASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS: ANALISIS RELIABILITAS, VALIDITAS, TINGKAT KESUKARAN DAN DAYA BEDA BUTIR SOAL - Loka Son, Aloisius (Gema Wiralodra, 2019)
A good assessment instrument is an instrument that can reveal data in accordance with the actual reality, is fixed, steady or reliable, and has varying degrees of difficulty and has a good index of discrimination. Therefore this study was conducted to analyze reliability, validity, level of difficulty, and differentiation of items that can be used to reveal students' mathematics problem solving abilities. The test questions tested are questions in the form of 4 numbers. The calculation results show that the 4 test questions for problem solving ability are reliability in the medium category, and valid with each category is high. The index has difficulty number 1 in the easy category, number 2 and 3 in the medium category, and number 4 in the difficult category, and the discrimination index is quite good